2017
DOI: 10.1088/1361-6560/aa7e5b
|View full text |Cite
|
Sign up to set email alerts
|

Systematic investigation on the validity of partition model dosimetry for90Y radioembolization using Monte Carlo simulation

Abstract: We aimed to investigate the validity of the partition model (PM) in estimating the absorbed doses to liver tumour ([Formula: see text]), normal liver tissue ([Formula: see text]) and lungs ([Formula: see text]), when cross-fire irradiations between these compartments are being considered. MIRD-5 phantom incorporated with various treatment parameters, i.e. tumour involvement (TI), tumour-to-normal liver uptake ratio (T/N) and lung shunting (LS), were simulated using the Geant4 Monte Carlo (MC) toolkit. 10 track… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The reason behind these discrepancies could be due to the simplification of PM estimation, where cross-fire irradiations between volumes were not considered. 10 Thus, from the MC simulation,it has been demonstrated that there are presence of beta radiations escaping from the regions where the 90 Y sources are deposited. This is supported by the isodose distribution as shown in Figure 17.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The reason behind these discrepancies could be due to the simplification of PM estimation, where cross-fire irradiations between volumes were not considered. 10 Thus, from the MC simulation,it has been demonstrated that there are presence of beta radiations escaping from the regions where the 90 Y sources are deposited. This is supported by the isodose distribution as shown in Figure 17.…”
Section: Resultsmentioning
confidence: 98%
“…A minimum of 1.0 × 10 7 histories should be generated in each simulation and repeated three times to ensure a statistical uncertainty of less than 1%. 10,[22][23][24][25][26] This is a common practice with Geant4 (or GATE) simulation, in which uncertainty of less than 1% is considered acceptable, as further reduction on the uncertainty (may be achieved by increasing the number of histories) comes with the cost of increased computational time, and that in most cases, lower uncertainty may not be achievable as MC simulation heavily rely on random events.…”
Section: F I G U R E 1mentioning
confidence: 99%
See 1 more Smart Citation
“…In this specific instance, a left-sided tumor included in the 99m Tc-MAA injection was not treated with 90 Y during this session. Overall, these results also demonstrate the necessity of using voxel-based dosimetry instead of compartmental models for 90 Y-microsphere radioembolization as distributions of activity are far from being uniform in liver sub-regions [ 50 ].…”
Section: Discussionmentioning
confidence: 98%
“…Charged particles resulting from the collapse of these radionuclides possess high energy with a short run-in substance. In this case, there is a sufficient number of α-and β-emitters in the immediate vicinity of tumor cells to ensure their destruction with minimal damage to the surrounding tissues 9,10 An important feature of lutetium's kinetics is that due to its low penetration range into tissues, it is effective in the treatment of small lesions and minimizes the impact of therapeutic doses on remote cells. 177 Lu is a beta-emitting radionuclide with an energy of 0.49 MeV and a half-life of 6.6 days (161 h).…”
Section: Foundations For the Application Of 177 Lu In Radionuclide Th...mentioning
confidence: 99%